A research on concentration and distribution of airborne particulate matter in Kuantan city - Rosman, Putri Shazlia; Abu Samah, Mohd Armi; Yunus, Kamaruzzaman (Blue Eyes Intelligence Engineering & Sciences Publication, 2019)
The development of Kuantan city had caused a great emission of particulate matter concentration to the Kuantan atmospheric. The airborne of particulate matter may causes immediate and long-term impacts on human health as it enters the lung through the respiratory tract. The larger particles more than 10um aerodynamic diameter can found in soot or smoke. In this study, the concentration of particulate matter (PM10) in the ambient air of Kuantan city was investigated using two continues monitoring station by the Department of Environment. The PM 10 data were taken for 15 years of study from year 2001-2016. Two (2) location of the continues monitoring station were used in the study where one in Indera Mahkota, Kuantan and another was in Balok Baru, Kuantan. In the study, the highest PM10 concentration was in year 2013 with 234.31 ug/m3 and the second highest in year 2015 with 271.62 ug/m3 for station 1. While, for station 2 the highest PM10 concentration were in year 2013 with 349.7 ug/m3 and the second highest in year 2015 with 328.46 ug/m3 respectively. The pattern distribution showed that the PM10 concentration between year 2013 to 2015 were absolutely outrages which was more than 300 ug/m3 was release in the atmospheric. The sources emission factor in this study can be from various sources and trans-boundary events may also be possible to cause the PM10 concentration disperse in Kuantan.